Sustainable Rice Farming Under Fertilizer Subsidy Policies: Assessing The Economic, Social, And Environmental Impacts - Rasda Rais; Seniorita; Mukmin Muhammad (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal